Komunikasi Tradisi Abda’u pada Prosesi HewanQurban Adat Tulehu Maluku - sulaeman, Sulaeman; Mahriani, Retna; Nurdin, Ali (Fakultas Dakwah IAIN Purwokerto, 2019)
Abda’u tradition is performed on the feast of Muslims’ Aidul Adha. This tradition is a form of struggle, the defense of the flag, seizure of the sacrificed animals’ blood by enforcing the ideological teachings of Islam. The purpose of this research was to understand and find communication events, communication components, and patterns of abda’u communication tradition on Maluku Tulehu to sacrifice animals’ procession. This research uses the theory of symbolic interactionism of the constructivist paradigm and communication ethnography method